Letter from Robert B. Potts to James Curtis Booth, November 13, 1855 - Potts, Robert B. (1855)
Potts writes James Curtis Booth (1810-1888) with the desire to obtain a sample of aluminum and to locate a feldspar deposit.
Keywords: Booth, James Curtis, 1810-1888; Aluminum; Feldspar